2015
DOI: 10.1080/09168451.2015.1062711
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and plasma kinetics of collagen tripeptide after peroral or intraperitoneal administration in rats

Abstract: Collagen tripeptide (CTP) is a collagen-derived compound containing a high concentration of tripeptides with a Gly-X-Y sequence. In this study, the concentrations and metabolites of CTP were monitored in rat plasma after its administration. We performed a quantitative analysis using high-performance liquid chromatography tandem mass spectrometry according to the isotopic dilution method with stable isotopes. We confirmed that the tripeptides Gly-Pro-Hyp, Gly-Pro-Ala, and Gly-Ala-Hyp were transported into the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…PEPT1 mediates tripeptide and dipeptide transport from the intestinal tract both in humans and in rats; therefore, we propose that Gly-Pro-Hyp was digested into Pro-Hyp in the blood and liver via the same mechanism as in rats, after being absorbed into blood in an intact form. 19) Various physiological roles have been described for Pro-Hyp 13,14) and our results indicate that administration of the Gly-Pro-Hyp precursor is a potentially effective means of delivering a high concentration of Pro-Hyp to the body. Although Ichikawa et al reported a Pro-Hyp T max of 2 h in their study monitoring metabolites in the blood after ingestion of fish-scale gelatin (molecular weight (MW) ca.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…PEPT1 mediates tripeptide and dipeptide transport from the intestinal tract both in humans and in rats; therefore, we propose that Gly-Pro-Hyp was digested into Pro-Hyp in the blood and liver via the same mechanism as in rats, after being absorbed into blood in an intact form. 19) Various physiological roles have been described for Pro-Hyp 13,14) and our results indicate that administration of the Gly-Pro-Hyp precursor is a potentially effective means of delivering a high concentration of Pro-Hyp to the body. Although Ichikawa et al reported a Pro-Hyp T max of 2 h in their study monitoring metabolites in the blood after ingestion of fish-scale gelatin (molecular weight (MW) ca.…”
Section: Discussionmentioning
confidence: 58%
“…In that experiment, we found that metabolites represented by Gly-Pro-Hyp, Pro-Hyp, and Gly-Pro appeared in the blood at comparable rates and concentrations for the two administration routes. 19) This result suggests that the body can absorb peptides efficiently if they are ingested in the tripeptide form. The beneficial effects of ingestion of collagen hydrolysate containing Gly-X-Y tripeptides include bone healing, 20) protection against photoaging, 21) anti-pruritus, 22) and decrease in atherosclerotic plaques.…”
mentioning
confidence: 99%
“…The tripeptide fraction (CTP) was isolated by reverse-phase HPLC. The mean molecular weight of CTP was approximately 300, and Gly-Pro-Hyp and Gly-Pro-Ala contents were 34% and 15%, respectively (Yamamoto et al 2015).…”
Section: Methodsmentioning
confidence: 94%
“…In fact, colonic bacteria have been shown to possess high proteolytic activities (Macfarlane, Cummings, & Allison, ), and amino acids and di‐ or tripeptides can be absorbed in mammalian distal colon by diffusion and the peptide transporter PEPT1, respectively (Binder, ; Wuensch et al., ). Orally administered glycine and Pro‐Hyp, which can be very efficiently absorbed in the small intestine (Craft, Geddes, Hyde, Wise, & Matthews, ; Yamamoto et al., ), should therefore induce higher peak concentrations of glycine and Pro‐Hyp in circulating blood than gelatin, and this may explain their superior anticolitis activities.…”
Section: Discussionmentioning
confidence: 99%